Bridging the gap: communities, forests and international networks - Center for International Forestry Research (Center for International Forestry Research, 2003)
This infobrief provides key points that few international networks have direct local impacts. Most focus on providing information and services to national level actors, helping develop resources and skills to promote national and local change. Better links between international, national and local levels need to be fostered. Networking has proved helpful in many countries but much more needs to be done to insert international policy gains into national reform platforms. Maintaining trust and links with and between communities requires investments of time and resources. Communications strategies need to ensure communities are being reached, without over-reliance on computers (which can exclude their effective participation). Community forestry and networking need sustained support to build social movements and community based links - support that promotes accountability without imposing artificial goals or structures. Participatory evaluation helps networks reflect on their effectiveness and ability to reach those they seek to include. Networks must take care to recognise their inherent limitations and also, not substitute themselves for the voice of local communities. Multi-stakeholder decision-making, new partnerships and engagements with civil society all promise new opportunities for local actors to have their voices heard but also entail further risks of social exclusion.